2015
DOI: 10.1186/s13002-015-0031-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal plants used by traditional healers in Phatthalung Province, Peninsular Thailand

Abstract: BackgroundIn rural communities of Thailand, traditional healers still play an important role in local health care systems even though modern medicine is easily accessible. Meanwhile, natural forests in Thailand which are important sources of materia medica are being greatly destroyed. This has led to an erosion of traditional Thai medicine. Furthermore, the concept of medicinal plant selection as medicine based on their tastes is still an important component of traditional Thai medicine, but no or little publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 76 publications
2
39
0
1
Order By: Relevance
“…Local health specialists are people of communities that are the most knowledgeable about traditional medicine and often about medicinal plants [2, 6, 8, 9, 10, 11], and, for this reason, they play an important role in the appreciation and dissemination of this knowledge. Healers, medicinal plant specialists and midwives are some examples of local health specialists [12].…”
Section: Introductionmentioning
confidence: 99%
“…Local health specialists are people of communities that are the most knowledgeable about traditional medicine and often about medicinal plants [2, 6, 8, 9, 10, 11], and, for this reason, they play an important role in the appreciation and dissemination of this knowledge. Healers, medicinal plant specialists and midwives are some examples of local health specialists [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in Thai traditional medicine for the treatment of fever. 4 Pharmacological study of leaf extracts revealed that it showed high anti-oxidant capacity in accordance with high flavonoid and phenolic compound contents. 5,6 These findings corresponded to the study by Singthong et al who found that water leaf extract of Tiliacora triandra provided phenolic compound and showed Cite this article : Katisart T, Rattana S. Hypoglycemic activity of leaf extracts from Tiliacora triandra in normal and streptozotocin-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…However, incessant collection of wild medicinal plants may result to its decline. As a response, cultivating these plants effectively conserves them and ensures its steady supply any time of the year [24][25][26] [27].…”
Section: A3 Plant Typementioning
confidence: 99%